KESEIMBANGAN KEHIDUPAN KERJA DITINJAU DARI BURNOUT PADA GURU PEREMPUAN DI KECAMATAN KOTA BANGUN - Muhammad Aulia; Miranti Rasyid (Universitas Muhammadiyah Gresik, 2024)
Background: Women as housewives and breadwinners are expected to have a balance at work and be able to fulfill their roles as wives and breadwinners. Objective: This study aims to determine the correlation between burnout and work-life balance in female teachers in Kota Bangun Sub-district. Method: This research method uses a quantitative approach. The subjects of this study were 63 female teachers in Kota Bangun Subdistrict who were selected using nonprobability sampling technique. The data collection method used was the work-life balance and burnout scale. The data analysis technique used was the Kendall Tau correlation test. The collected data were analyzed with the help of the Statistical Package for Social Science version 26.0 for windows program. Results: The results showed that the r value was -0.415 and the sig value was 0.000 (p<0.05) which means that there is a significant correlation with a moderate category between burnout and work-life balance in female teachers in Kota Bangun District. Conclusion: As for this study, the correlation that occurs in the direction of a negative correlation, which means that the lower the burnout, the higher the work-life balance and vice versa, the higher the burnout, the lower the work-life balance.